1972
DOI: 10.1149/1.2404149
|View full text |Cite
|
Sign up to set email alerts
|

The Anodic Oxide of Iron: Its Component Layers and Their Properties

Abstract: The anodic oxidation of an iron electrode in a neutral borate electrolyte is studied using a following ellipsometer. The oxide film is found to consist of two layers with different refractive indices: an outer layer of Fe2O3 and a thicker inner layer of Fe3O4 . A thin layer of Fe3O4 is grown on the electrode in the active state, and the electrode passivates when a partial monolayer of Fe2O3 is grown at the Fe3O4‐normalelectrolyte interface. Passive state anodic oxidation causes simultaneous growth of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0
2

Year Published

1972
1972
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 9 publications
2
14
0
2
Order By: Relevance
“…Given the expected reactions involving oxidation of Fe(OH) 2 → Fe 3 O 4 and the observation of Fe 3 O 4 in previous studies of the passive film on iron in neutral borate and 1 M alkaline solutions,6, 7, 9, 13, 24 it is somewhat surprising that no Fe 3 O 4 was fitted in the MCR optimization. The absence of Fe 3 O 4 bands may be the result of oxidation of the outer part of Fe 3 O 4 to γ‐Fe 2 O 3 ,8 which would agree with the two‐layer model,44, 45 with an inner layer composed of Fe 3 O 4 and γ‐Fe 2 O 3 with the Fe 3 O 4 adjacent to the metal surface and the γ‐Fe 2 O 3 adjacent to and underneath a layer of a loosely bound outer layer of FeOOH, so that the Fe 3 O 4 is not detected even though it may be present.…”
Section: Discussionsupporting
confidence: 55%
“…Given the expected reactions involving oxidation of Fe(OH) 2 → Fe 3 O 4 and the observation of Fe 3 O 4 in previous studies of the passive film on iron in neutral borate and 1 M alkaline solutions,6, 7, 9, 13, 24 it is somewhat surprising that no Fe 3 O 4 was fitted in the MCR optimization. The absence of Fe 3 O 4 bands may be the result of oxidation of the outer part of Fe 3 O 4 to γ‐Fe 2 O 3 ,8 which would agree with the two‐layer model,44, 45 with an inner layer composed of Fe 3 O 4 and γ‐Fe 2 O 3 with the Fe 3 O 4 adjacent to the metal surface and the γ‐Fe 2 O 3 adjacent to and underneath a layer of a loosely bound outer layer of FeOOH, so that the Fe 3 O 4 is not detected even though it may be present.…”
Section: Discussionsupporting
confidence: 55%
“…Staehle and co-workers (5), using Auger analysis, concluded that the film was duplex in nature. This conclusion had also been reached by Ord (6) using ellipsometry. In other work, Kruger (7) suggested that the film contained a small amount of hydrogen and postulated, following Bloom (8), that the outer layer of 7-Fe20~ was stable only if it contained a small amount of H (~0.06%).…”
supporting
confidence: 59%
“…As an option for treating chlorinated solvents in groundwater, iron powder showed clear promise as it could dehalogenate these compounds (Ho & Ord, 1972). However, iron powder is limited in how it can be handled, especially in how water can be filtered through it.…”
Section: Introductionmentioning
confidence: 99%